The impact of emotion management ability on learning engagement of college students during COVID-19 - Lei, Xiaochun (Frontiers in Psychology, 2022)
During the COVID-19, the wanton spread of novel coronavirus had a huge negative effect on the emotions of college students, resulting in a serious impact on the daily learning behavior of many college students. In this context, college students’ emotion management ability is particularly important. Therefore, based on the results of a questionnaire survey of 580 college students, the present study conducts an in-depth analysis of the relationship between current college students’ emotion management ability and learning engagement, and explores the mediating role of psychological safety and self-efficacy in the relationship between emotion management ability and learning engagement. The results show that college students’ emotion management ability is significantly positive related to learning engagement, psychological safety and self-efficacy; Psychological safety and self-efficacy can play a partial mediating role between emotion management ability and college students’ learning engagement. The results reveal the importance of good emotion management ability of college students during the COVID-19, and enlighten colleges and universities to actively pacify students’ emotions to promote their normal learning.